United Arab Emirates Keys to Soil Taxonomy - Shahid, Shabbir A.; Abdelfattah, Mahmoud A.; Wilson, Michael A.; Kelley, John A.; Chiaretti, Joseph V.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
Central to human life and civilization, soils are an integral part of the physical and cultural environment. Although we may take them for granted, the rise and fall of civilizations is closely linked with the use and abuse of soil and water resources. It is therefore important to evaluate soils for their quality and link them to appropriate uses and services. This book provides information on soil classification and shows how to key out taxa relevant to UAE soils. The latest soil inventory of United Arab Emirates reveals that a rather uniform looking desert landscape has, in fact, a diversity of subsurface features. These features confirm the soil diversity in terms of classification, chemistry, physics, mineralogy, fertility, suitability for different uses and vulnerability to land degradation. United Arab Emirates Keys to Soil Taxonomy presents information for keying out the soils of the United Arab Emirates into separate classes and provides a guide to associated laboratory methods. The classification used predominantly is extracted from the 11th edition of the USDA-NRCS Keys to Soil Taxonomy, and sections relevant to the soils found in the UAE are included here. Primarily, this key is designed to fit the soil system of the United Arab Emirates. Information not found in the USDA key has been added, including criteria and classes for: 1) differentiating anhydritic soils from gypsic soils, 2) identifying (3z(Blithic(3y (Bsubgroups for Aquisalids and Haplosalids, 3) identifying (3z(Bsalidic(3y (Bsubgroups within the great groups of Gypsids, Calcids, Psamments, and Orthents, and 4) incorporation of phases for soil taxa. A subsurface diagnostic horizon and mineralogy class (anhydritic), not reported earlier in the world soil literature and, recently found in the UAE, has also been added to the book. The book also offers a mechanism for updating the current soil surveys, and will facilitate the correlation of soils from new surveys in the UAE. Additionally, it will help the international soil science community to converse about UAE soils, and facilitate comparison to soils of other regions. These linkages allow countries with similar mapping and classification procedures and similar soils to transfer agriculture technology without conducting long-term experiments under similar environmental conditions, especially for Gulf Cooperation Council countries (Bahrain, Kuwait, Qatar, Oman, and Saudi Arabia).s
1 Soil Classification -- 2 The Soils That We Classify -- 3 Horizons, Layers, and Characteristics Diagnostic for the Higher Categories -- 4 Family and Series Differentiae -- 5 Identification of the Taxonomic Class of a Soil -- 6 Laboratory Methods for Classification of United Arab Emirates -- 7 Soil Families and Soil Series of the United Arab Emirates -- Index.
Keywords: Environmental sciences; Geography; Geographical information systems; Regional planning; Ecology; Soil conservation; Environment; Soil Science & Conservation; Landscape/Regional and Urban Planning; Environmental Science and Engineering; Geoecology/Natural Processes; Geographical Information Systems/Cartography.; Geography (general).